Racial/ethnic inequities in continuity and site of care: location, location, location. - Doescher, M P (2001)
OBJECTIVE: To examine how continuity of care with the same provider varies by race/ethnicity and by site of care. DATA SOURCES/STUDY SETTING: Secondary data analyses of the 1996-97 Community Tracking Study household survey, a representative cross-sectional sample of 34,858 U.S. adults (aged 18 to 64 years), were employed. STUDY DESIGN: Logistic regression analyses were conducted to explore relationships between respondents' race/ethnicity and having a regular site of care, type of site, and continuity with the same provider at this site. PRINCIPAL FINDINGS: Racial/ethnic minority group members were less likely than whites to identify a regular site of care. Among respondents who identified a regular site, minorities, particularly Spanish-speaking Hispanics, reported less continuity of care with the same provider. However, these disparities in continuity were largely explained by racial/ethnic differences in the types of places where care was obtained. Compared to those who were seen in physicians' offices, continuity with the same provider was much lower among respondents who were seen in hospital out patient departments or health centers or other clinics. CONCLUSIONS: Racial and ethnic minority group members receive less continuity of care for reasons including lack of a regular site of care and less continuity with the same provider. Greater use of hospital clinics and community health centers by minorities also contributes to this discontinuity.